Clinical Outcomes of Proton Radiotherapy for Uveal Melanoma. Issue 8 (August 2016) - Verma, V.; Mehta, M.P.
Abstract: Aims: Although clinical experience with proton beam radiotherapy (PBT) for most tumours is limited, there is relatively longstanding experience for uveal melanomas. Because of potential to reduce ocular toxicities, PBT is an attractive option for these tumours. However, summative data remain scarce. We systematically reviewed clinical outcomes of uveal melanoma patients treated with PBT, to comprehensively assess outcomes such as tumour control, survival, enucleation rates, toxicity and visual acuity preservation. Materials and methods: A systematic search of PubMed, EMBASE, abstracts from meetings of the American Societies for Radiation Oncology and Clinical Oncology, and the Particle Therapy Co-Operative Group was conducted from 2000 to 2015. Fourteen original investigations from 10 different institutions were analysed. Results: Most tumours were choroidal and medium-/large-sized, and received 50–70 Cobalt Gray equivalent dose; more recent data reported lower doses. Five year local control rates exceed 90%, which persisted at 10 and 15 years. Five-year overall survival rates ranged from 70 to 85%, 5 year metastasis-free survival and disease-specific survival rates from 75 to 90%, with more recent series reporting higher values. With the removal of smaller studies, 5 year enucleation rates were consistently between 7 and 10%. Many patients (60–70%) showed a post-PBT visual acuity decrease, but still retained purposeful vision (>20/200); more recent, higher-volume series reported superior numbers. Complication rates were quite variable but showed improvements on historical plaque brachytherapy data. Only one randomised trial directly compared particle therapy (helium) with plaque brachytherapy, showing the former to be superior; this is addressed separately. Conclusions: PBT is an excellent modality to treat uveal melanomas, with high survival outcomes and visual acuity preservation. Although there are low toxicity and enucleation rates, the recent development of supportive therapies for radiation toxicities can further decrease clinical adverse effects. Highlights: Proton beam radiation can reduce ocular toxicities in patients with uveal melanoma. Five-year local control rates exceed 90%, which persist at 10- and 15- years. Five-year overall survivals range from 70–85% using proton beam radiotherapy. Only 7–10% of uveal melanoma patients need eye removal after treatment. Post-treatment complications and vision preservation are acceptable.